Measurements of pulsed electron beams emitted from plasma-focus devices - Jakubowski, L.; Sadowski, M.J. (Вопросы атомной науки и техники, 2005)
A dense plasma column, which is formed by a pulsed discharge within facilities of the Plasma-Focus (PF) type, is a source of the intense X-ray emission, pulsed electron beams and ion streams. Investigation of the electron beams can deliver information about development of plasma instabilities, which induce the formation of high-temperature plasma micro-regions in the form of hot-spots and/or filaments. The paper reports on recent studies of the pulsed electron beams within PF-type facilities. Шнур щільної плазми, формований імпульсним розрядом на установках типу плазмовий фокус (ПФ), є джерелом інтенсивного рентгенівського випромінювання, імпульсних електронних пучків і потоків іонів. Дослідження електронних пучків може дати інформацію про розвиток плазмових нестійкостей, що викликають формування високотемпературних плазмових мікрообластей у виді «гарячих плям» і/або волокон. Робота присвячена останнім результатам вивчення імпульсних електронних пучків, генерируємих в установках типу ПФ. Шнур плотной плазмы, формируемый импульсным разрядом на установках типа плазменный фокус (ПФ), является источником интенсивного рентгеновского излучения, импульсных электронных пучков и потоков ионов. Исследование электронных пучков может дать информацию о развитии плазменных неустойчивостей, которые вызывают формирование высокотемпературных плазменных микрообластей в виде «горячих пятен» и/или волокон. Работа посвящена последним результатам изучения импульсных электронных пучков, генерируемых в установках типа ПФ.